2011
DOI: 10.1097/crd.0b013e3181fb7eb8
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction

Abstract: Previous studies have shown an increased incidence of erectile dysfunction (ED) among patients diagnosed with cardiovascular disease (CVD). Both conditions, which may be a consequence of underlying endothelial dysfunction, share many risk factors such as hypertension, dyslipidemia, diabetes, depression, obesity, and cigarette smoking. Because vascular disturbance of the penile endothelium leads to ED, the possibility arises that ED may be an early indicator for systemic endothelial dysfunction and subsequent C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(19 citation statements)
references
References 68 publications
0
15
0
4
Order By: Relevance
“…Furthermore, much evidence suggests that vascular abnormalities such as endothelial dysfunction and atherosclerosis play a critical role in both conditions (3, 5). Importantly, the concept that ED is a prior indicator of CVD is growing stronger (6)*.…”
Section: A-introductionmentioning
confidence: 99%
“…Furthermore, much evidence suggests that vascular abnormalities such as endothelial dysfunction and atherosclerosis play a critical role in both conditions (3, 5). Importantly, the concept that ED is a prior indicator of CVD is growing stronger (6)*.…”
Section: A-introductionmentioning
confidence: 99%
“…Penile erection occurs when there is a relaxation of the smooth muscle cells in cavernosal arterioles and surrounding sinuses, resulting in increased blood flow into the penis associated with a pressure-dependent veno-occlusive mechanism within the sinuses controlling the blood outflow [ 1 , 2 ]. The major mechanism responsible for ED is an increase in the tone and/or contractility of the smooth muscle within the corpus cavernosum and penile arteries [ 3 ], which is mostly due to diminished production and function of nitric oxide (NO) and other vasoprotective factors, which is compounded by the exaggerated production of reactive oxygen species (ROS) and vasoconstrictors [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, both choroid and penis have a rich vasculature and impaired microcirculation has been disclosed in the choroids of patients with neovascular AMD and in the penises of men with ED [2224]. Second, some recent studies have demonstrated that disorders with endothelial dysfunction are associated with ED [25].…”
Section: Discussionmentioning
confidence: 99%